The Distribution of Power Over Social Distancing Regulation in the UK: Constitutional Design Principles from Economic Theory - Andrew Smith; Graham Alan Brownlow (Queen's University Belfast, Queen's Management School, 2021)
Which groups of elected officials should be in charge of decisions about the imposition of lockdowns and other social distancing rules? People throughout the UK have debated this issue since the start of the pandemic. When central government, local governments, and devolved administrations all enjoy democratic legitimacy, disputes over who should have the power to impose social distancing rules are almost inevitable. The nature of the British constitution also means that the recent debates about parliamentary insight and social distancing rules were predictable. This paper sheds lights on these debates over who should have the power to impose social distancing rules by drawing on economic theory, particularly the work of Nobel Laureates Hayek (1945) and Ostrom (1990). We review UK policy since March 2020 using this lens and then present policymakers with actionable recommendations. We argue that local rather than national governments should be given authority over whether or not to impose lockdowns and similar measures. We argue that in areas in which local government powers are not unified into a single unit and instead dispersed to different levels (e.g. county and borough councils), power over social distancing rules should be vested in the most junior unit of government. We use economic theory to argue that the legislative branches within each level of government should exercise close and continuous parliamentary oversight of all social distancing rules. In light of this pandemic, the UK might also consider investing resources in acquiring a written constitution that would clearly specify who has power over public health measures such as social distancing rules
Keywords: 330